Strategic Recruitment Practices and Lean Hospital Performance: The Mediating Role of Patient-Centered Care in Private Hospitals - Puni Oktisari; Ferdi Antonio (Indonesian Journal Economic Review (IJER), 2026)
Despite growing attention to lean healthcare, limited empirical evidence explains how recruitment practices create operational and business value. This study examines how strategic recruitment practices influence lean hospital performance through the mediating role of patient-centered care (PCC). Recruitment is conceptualized through recruitment transparency, procedural justice, and previous work experience. A quantitative survey was conducted using purposive sampling of 221 experienced nurses recruited within the last two years from six Type B private hospitals in Jakarta. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that recruitment practices significantly enhance PCC, which in turn drives lean hospital performance. Procedural justice has the strongest effect on PCC (β = 0.472, p < 0.001), followed by recruitment transparency (β = 0.370, p < 0.001). PCC significantly improves lean hospital performance (β = 0.353, p < 0.001), confirming its central mediating role. Notably, procedural justice has no significant direct effect on lean performance (β = -0.061, p > 0.05), indicating full mediation through PCC. Other recruitment dimensions show smaller but significant direct and indirect effects. The findings highlight that recruitment creates value not directly, but by fostering patient-centered behaviors that enhance efficiency, service quality, and overall hospital performance. The study contributes to HR and healthcare management literature by positioning recruitment as a strategic driver of lean healthcare outcomes.